2013
DOI: 10.1002/oby.20524
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the mediators of asthma in obesity and obesity with type 2 diabetes: Reduction with weight loss

Abstract: Objective: To determine whether the expression of key asthma related genes, IL-4, LIGHT, LTBR, MMP-9, CCR-2, and ADAM-33 in mononuclear cells and the plasma concentration of nitric oxide metabolites (NOM) and MMP-9 are increased in the obese, obese type 2 diabetics (T2DM) and in morbidly obese patients prior to and after gastric bypass surgery (RYGB). Design and Methods: The expression of these genes in MNC and plasma concentrations of these indices was measured in healthy lean and in obese with and without T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 26 publications
0
48
0
Order By: Relevance
“…There is mounting evidence indicating the beneficial effects of the cytokine TNFSF14 in disease . However, the role of TNFSF14 in the development of obesity and type 2 diabetes remains poorly understood . Our novel findings provide clear evidence that TNFSF14 is elevated in mice as an adaptive response to attenuate characteristics of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…There is mounting evidence indicating the beneficial effects of the cytokine TNFSF14 in disease . However, the role of TNFSF14 in the development of obesity and type 2 diabetes remains poorly understood . Our novel findings provide clear evidence that TNFSF14 is elevated in mice as an adaptive response to attenuate characteristics of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 61%
“…Currently controversy surrounds the role of TNFSF14 in the development of the metabolic syndrome. Serum TNFSF14 levels are reportedly increased in morbidly obese humans and the expression of TNFSF14 is reduced in patients who do not have T2D compared with type 2 diabetic patients . However, it remains to be elucidated whether TNFSF14 is functionally altered in the progression of the metabolic syndrome in a pro‐ or anti‐obesogenic manner.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Dandona et al demonstrated that following GBP and weight loss, there is a reduction in the expression of key genes involved in asthma pathogenesis including IL-4, MMP-9, LIGHT, LTBR, and ADAM-33 [134]. Because of these changes in gene expression, GBP may provide a potential therapeutic approach to asthma in the morbidly obese.…”
Section: Chapter 3: Specific Considerations and Indications For Surgementioning
confidence: 99%
“…Leitner et al () observed a deep increase of MMP‐9 levels in adipose tissue from obese donors, which improve Osteopontin (OPN) inflammatory and pro‐diabetic effects on adipocytes. Dandona et al () also found high levels of MMP‐9 in plasma from obese patients, with or without diabetes, directly associated with plasma nitric oxide metabolites levels positively related with responsivity to surgical therapy. Rouault et al () observed that blood neutrophils from obese subjects release high levels of MMP‐9 and other pro‐inflammatory mediators (IL‐8, CCL2, MPO, etc.)…”
Section: Estrogen Receptors: “Genomic” and “Non‐genomic” Actions In Rmentioning
confidence: 93%